2008
DOI: 10.1007/s10658-008-9268-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the incidence of latent infections caused by Monilinia spp. and the incidence of brown rot of peach fruit: factors affecting latent infection

Abstract: Five field experiments were performed in commercial orchards located in Lleida (Spain) over three growing seasons, 2000-2002, in order to estimate the relationship between the incidence of latent infection caused by Monilinia spp. in peaches and the incidence of post-harvest brown rot. No latent infection was recorded at popcorn and the maximum incidence occurred pre-harvest; in some orchards a second peak was detected during the pit hardening period. Monilinia laxa is the most prevalent species isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 21 publications
1
97
0
2
Order By: Relevance
“…We assumed a fruit to be susceptible to infection from the time t i at which P(FD) = 0.1, with FD assumed to be a linear function of time, until the time of fruit harvest t H . We assumed as favorable those days when precipitations occurred and mean temperature was comprehended between 22 and 26 • C in accordance to previous studies indicating that conidia reproduction preferably occurs in wet conditions (Tamm and Flückiger, 1993;Xu and Robinson, 2000;Gell et al, 2008;Holb, 2008) and that it is impaired at "extreme" temperatures that are likely to be met in those days with mean daily temperature <22 or >26 • C (Tamm and Flückiger, 1993;Holb, 2008). Eventually we computed how many favorable days for brown rot spreading occurred in 2014 and 2015, (i.e., number of rainy days with mean temperature between 22 and 26 • C in the time period t i -t h ).…”
Section: Discussionsupporting
confidence: 54%
“…We assumed a fruit to be susceptible to infection from the time t i at which P(FD) = 0.1, with FD assumed to be a linear function of time, until the time of fruit harvest t H . We assumed as favorable those days when precipitations occurred and mean temperature was comprehended between 22 and 26 • C in accordance to previous studies indicating that conidia reproduction preferably occurs in wet conditions (Tamm and Flückiger, 1993;Xu and Robinson, 2000;Gell et al, 2008;Holb, 2008) and that it is impaired at "extreme" temperatures that are likely to be met in those days with mean daily temperature <22 or >26 • C (Tamm and Flückiger, 1993;Holb, 2008). Eventually we computed how many favorable days for brown rot spreading occurred in 2014 and 2015, (i.e., number of rainy days with mean temperature between 22 and 26 • C in the time period t i -t h ).…”
Section: Discussionsupporting
confidence: 54%
“…Under unfavourable weather conditions, the primary infections may remain latent in the blossoms and/or immature fruit (Emery et al, 2000;Gell et al, 2008), and persist as latent infections throughout the growing season until the weather conditions become conducive to disease expression Luo et al, 2001b;Luo and Michailides, 2003). The occurrence of latent infections is very important for the epidemiology of the disease as several studies have shown (Emery et al, 2000;Luo et al, 2001a and b;Northover and Cerkauskas, 1994).…”
Section: Biology and Epidemiology Of M Fructicolamentioning
confidence: 99%
“…The incidence of latent infections on immature fruit and the incidence of brown rot on fruit at harvest and post-harvest are also influenced by the quantity of inoculum, the fruit phenological state (Biggs and Northover, 1988;Emery et al, 2000;Gell et al, 2008;Luo and Michailides, 2003;Ogawa et al, 1995), and the environmental conditions (temperature and wetness duration) Luo and Michailides, 2003;Wade and Cruikshank, 1992). Temperature and wetness duration are considered the most crucial factors affecting fruit infection by M. fructicola (Biggs and Northover, 1988a;Michailides, 2001, 2003).…”
Section: Latent Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on appressorial formation by M. fructicola have focused on the surface properties of the fruit, the stage of fruit maturity, and the signaling pathways that are required for surface attachment and appressorial formation (Cruickshank and Wade, 1992;Lee and Bostock, 2006). The incidence of brown rot increases as fruit approaches maturity (Gell et al, 2008;Lee and Bostock, 2007;Villarino et al, 2011): immature fruit are more resistant to infection than mature fruit (Gell et al, 2008;Bostock, 2006, 2007;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%